Effect of probiotics on the nutritional status of severe stroke patients with nasal feeding that receive enteral nutrition: A protocol for systematic review and meta-analysis of randomized controlled trials. Issue 17 (30th April 2021) - Liu, Xiaomin; Zhang, Yasu; Chu, Jiahao; Zheng, Jie; Cheng, Xue; Li, Xinmin; Long, Junzi
Abstract: Background: Malnutrition is commonly observed after stroke and is closely associated with poor clinical outcomes. So, early nutrition support is particularly crucial for severe stroke patients. However, a significant number of critically ill patients are intolerant to enteral nutrition (EN). Probiotics have been widely used in malnutrition by various diseases and have a low incidence of enteral intolerance. So, we aim to elucidate the efficacy of probiotics in EN in improving the nutritional status and clinical prognosis of severe stroke patients with nasal feeding. Method: Embase, PubMed, Sinomed, Web of Science, Cochrane Library, China National Knowledge Infrastructure, Wanfang database, and Vip Journal Integration Platform were searched from inception to March 31, 2021. Randomized controlled trials that applied probiotics in patients with severe stroke were included. The data were extracted and the risk of bias was assessed independently by 2 evaluators. Results: Twenty-four studies comprising 2003 participants of randomized controlled trials were included. The result of pooled analyses showed that probiotics in EN were associated with better outcomes than EN alone on Glasgow Coma Scale score (mean difference [MD] = 1.03, 95% confidence intervals [CI]: 0.78–1.27; P  < .00001), infection events (odds ratio [OR] = 0.25, 95% CI: 0.15–0.43; P  < .00001), rate of intestinal flora dysbiosis (OR = 0.24, 95% CI: 0.12–0.48; P  < .0001), gastrointestinal complications (OR = 0.25, 95% CI: 0.16–0.37, P  < .00001), time to reach target nutrition (MD = −1.80, 95% CI: −2.42 to 1.18, P  < .00001), prealbumin content (MD = 25.83, 95% CI: 13.68–37.99, P  < .0001). Conclusion: Our results demonstrated that probiotics supplementation might be an effective intervention for improving the clinical prognosis in severe stroke patients with nasal feeding, but no significant effect on increasing muscle circumference. Abstract : Supplemental Digital Content is available in the text